2018
DOI: 10.1073/pnas.1808426115
|View full text |Cite
|
Sign up to set email alerts
|

Heme ameliorates dextran sodium sulfate-induced colitis through providing intestinal macrophages with noninflammatory profiles

Abstract: SignificanceFollowing hemorrhage in damaged tissues, hemoglobin induces macrophages (Mϕs) possessing ability to protect against tissue inflammation. Hemorrhage-appearing mucosa is observed in patients with inflammatory bowel disease. However, heme-mediated modulation of intestinal Mϕ activity remains poorly understood. Here, we provide evidence that Spi-C induced by heme is a key molecule for providing noninflammatory gene expression patterns of intestinal CX3CR1high Mϕs. We found that the Spic deficiency in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…However, the level of TNFα in the colon was unchanged in orange pectin-fed mice (Figure 7I). Knowing that intestinal macrophages have been reported to supply IL-6 and raise the inflammatory response in DSS-induced colitis (46), these results indicated that orange pectin regulates IL-6 production in colon, thereby attenuating the inflammatory response.…”
Section: Orange Pectin Not Citrus Pectin Ameliorates Dss-induced Comentioning
confidence: 72%
See 1 more Smart Citation
“…However, the level of TNFα in the colon was unchanged in orange pectin-fed mice (Figure 7I). Knowing that intestinal macrophages have been reported to supply IL-6 and raise the inflammatory response in DSS-induced colitis (46), these results indicated that orange pectin regulates IL-6 production in colon, thereby attenuating the inflammatory response.…”
Section: Orange Pectin Not Citrus Pectin Ameliorates Dss-induced Comentioning
confidence: 72%
“…A recent report showed that intestinal macrophage subsets are involved in the initiation of murine colitis (34). Furthermore, Kayama et al reported that CX3CR1 + intestinal macrophages were able to produce high concentrations of IL-1β and IL-6 via activation of TLR4, and that suppression of this pathway resulted in the amelioration of DSS-induced colitis (46). Our present results showed that colonic IL-6 levels were decreased in orange pectin-fed mice both in TNBS-and DSSinduced colitis (Figures 5E, 7H).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of heme and subsequent induction of HO-1 in peritoneal macrophages alleviated inflammation in a choline-deficient diet mouse model of pancreatitis [91]. Similarly, peritoneal administration of heme was found to protect against experimental colitis via up-regulation of Spi-C in macrophages [92]. The anti-inflammatory effects of Spi-C are mediated by its association with the interferon regulatory factor (IRF)5, thereby blocking the interaction of IRF5 with the NF-kB subunit p65, which is required for the transcriptional regulation of pro-inflammatory genes such as IL-6 and IL-1α.…”
Section: Heme As An Anti-inflammatory Signal In Macrophagesmentioning
confidence: 93%
“…The anti-inflammatory effects of Spi-C are mediated by its association with the interferon regulatory factor (IRF)5, thereby blocking the interaction of IRF5 with the NF-kB subunit p65, which is required for the transcriptional regulation of pro-inflammatory genes such as IL-6 and IL-1α. Similar to RPMs, intestinal macrophages also exhibit high basal levels of Spi-C suggesting that heme might also be a functional demand signal required for the intestinal macrophage phenotype in physiological conditions [92]. This might further contribute to the non-inflammatory status of these cells which may allow their co-existence with the gut microbiome.…”
Section: Heme As An Anti-inflammatory Signal In Macrophagesmentioning
confidence: 99%
“…98 Interestingly, hemoglobin released from hemorrhaging tissue in experimental colitis limits pro-inflammatory gene expression in Cx3cr1 high macrophages, thus limiting intestinal inflammation in DSS-induced colitis. 99 As in the healthy gut, however, resident macrophages may contribute to the recruitment of monocytes through release of CCR2 ligands. This has been demonstrated in the case of the specialized niche of CD169 + macrophages located preferentially around the base of intestinal crypts, adjacent to blood vessels and lymphatics, that have been shown to produce CCL8 in response to inflammation or injury to attract inflammatory Ly6C high monocytes ( Figure 3B).…”
Section: Lamina Propria Macrophages In Intestinal Inflammation and mentioning
confidence: 99%